Range of motion and sticking region effects on the bench press load-velocity relationship - Martinez-Cava, A.; Morán-Navarro, R.; Hernández-Belmonte, A.; Courel-Ibanez, J.; Conesa-Ros, E.; González-Badillo, J. J.; Pallarés, J. G. (Journal of Sports Science & Medicine, 2019)
This study aimed to analyze the influence of range of motion (ROM) on main biomechanical parameters of the bench press (BP) exercise: i) load-velocity relationship by mean (MV) and mean propulsive velocity (MPV), ii) one-repetition maximum strength (1RM); iii) contribution of the propulsive and braking phases, and iv) presence of the sticking region key parameters (first peak barbell velocity: Vmax1, minimum velocity: Vmin and second peak barbell velocity: Vmax2). Forty-two strength-trained males performed a progressive loading test, starting at 20 kg and gradually increasing the load in 10 kg until MPV = 0.50 m·s-1 and 5 down to 2.5 kg until 1RM, in three different ROMs: full ROM (BPFULL), two-thirds (BP2/3) and one-third (BP1/3). While significant differences were detected in the velocity attained against loads between 30-95% 1RM (BPFULL, BP2/3 and BP1/3, p < 0.05), both MV and MPV showed a very close relationship to %1RM for the three BP variations (R2 = 0.935-0.966). The contribution of the braking phase decreased progressively until it completely disappeared at the 80%, 95% and 100% 1RM loads in BP1/3, BP2/3 and BPFULL, respectively. The 1RM increased as the ROM decreased (BPFULL < BP2/3 < BP1/3, p < 0.05). Despite the three biomechanical parameters that define the sticking region on the velocity-time curves were only observed in BPFULL variation, in 54.5% of the cases the subjects started their BP2/3 displacement before reaching the position at which the Vmin occurs in their BPFULL exercise. The complete or partial presence of the sticking region during the concentric action of the lift seems to underlie the differences in the 1RM strength, load-velocity profiles and the contribution of the propulsive phase in the BP exercise at different ROMs. Key Points